Duties And Responsibilities Of Customary Functionaries In The Implementation Of The Indigenous Government System In Nafri Village - Awi, Sara Ida Magdalena; Windia, I Wayan; Dewi, A. A Istri Ari Atu; Parwata, A. A Gede Oka; Nurcahyo, Edy (International Journal of Educational Research & Social Sciences, 2022)
The purpose of writing this article is to find out the role of customary functionaries in running the customary government system and the cooperative relations between these traditional partners in carrying out the customary government system for the indigenous people in Nafri Village. Both traditional partners from Nafri Village and also traditional partners from outside Nafri Village. This research can be categorized in the type of research with empirical aspects, because here we see the role of customary functionaries in the implementation of customary government law in the Nafri customary law community who sees the role of customary functionaries being carried out in reality. From the results of the study, it was revealed that customary functionaries have a very important role in carrying out the customary government system in the indigenous people of Nafri Village, both on ontofro and whase ontofro. And also these traditional functionaries have a cooperative relationship with traditional partners, both those from within the Nafri village itself and also traditional partners with villages from outside the Nafri village.